Efektivitas Permainan Bongkar Pasang Huruf Hijaiyah terhadap Diskriminasi Visual Anak Usia 3–4 Tahun - Siti Martatik; Eka Danik Prahastiwi (ALSYS, 2026)
This study aims to analyze the effectiveness of the Hijaiyah letter matching game in improving the visual discrimination ability of children aged 3–4 years at KB Putra Utama II. This study used a quantitative approach with a one-group pretest-posttest quasi-experimental design. The research subjects consisted of 15 children selected using the total sampling technique. Data were collected through observation and developmental assessment sheets, and were then analyzed descriptively by comparing the pretest and posttest results. The results showed that before the treatment, most children still had difficulty recognizing and distinguishing Hijaiyah letters with similar forms. After the treatment was administered, the children’s visual discrimination ability improved, as indicated by the increasing number of children in the good category and the rise in the average score from 55 to 82. In addition, the children also became more active and enthusiastic in learning. This study concludes that the Hijaiyah letter matching game is effective as a learning medium for improving the visual discrimination ability of early childhood and provides implications for educators to develop game-based learning that is interactive and appropriate to children’s characteristics.